Norms in AVT: A dual approach to a long-lasting and fundamental notion - Martí Ferriol, José Luis (Journal of Audiovisual Translation, 2020)
The main objective of this article is to review the concept of norm in Audiovisual Translation (AVT), a concept which has been subject to a dual approach when using it, both a descriptive one and a prescriptive one. The review proposed in this article is intended to be twofold: descriptive and critical. A descriptive approach will be the focus in the first two sections of the paper, where the history and evolution of the concept is analysed. A more critical stance is then adopted in the following two sections of the paper. The dual orientation of the concept of norm is highlighted in Section 3. The hypothetical application of norm theory to professional practices for the main modes within AVT has in most cases taken the form of guidelines, the result of a pure prescriptive approach. This discussion is covered in Section 4. The final fifth section summarizes the review, while pointing out the great significance of this fundamental notion within the field of AVT. All in all, the concept has proven to be successful and long-lasting, and it is mainly accepted that norms obtained from empirical research should give rise to guidelines for professional practice in translation.